European Tourism Sector Development in the Context of Energy Uncertainty - Kocourková, Michaela; Kuziboev, Bekhzod; Matniyozov, Murodjon (International Journal of Energy Economics and Policy, 2024)
The research is a novel to study the impact of energy uncertainty on international tourism receipt in 11 European countries namely Belgium, Croatia, Denmark, France, Germany, Greece, Ireland, Italy, Netherlands, Spain and Sweden due to availability of energy uncertainty index data recently developed by Dang et al. (2023). As econometric tool, we employ a Fully Modified Ordinary Least Squares (FMOLS) framework and include obtained long-run relations in a panel Vector Error Correction model (VECM). The findings suggest that 1% increase in energy uncertainty leads to 0.08% decrease in international tourism receipt in Europe. Moreover, international tourism receipt reaches the equilibrium with the adjustment speed of 23% annually. Regarding the effect of control variables, economic development has a negative relation whereas CO2 emissions and institutional quality have a positive association with international tourism receipt. As a policy implication, enhancing renewable energy is suggested to cope with energy uncertainty consequences that might affect tourism development.